The Significance of Research Based Community Practice in Indian Social Work Education - George, Jasmine (Journal of Social Work Education and Practice, 2023)
The Social Work profession promotes social change, problem solving in human relationships and the empowerment and liberation of people to enhance wellbeing. Social work as a profession in India is yet to get its due recognition from the government and society. Indian Social work practice and education seeks some kind of constructive changes. This paper explores the importance of community practice in social work education in Indian context. To fulfill a commitment to the community concept, social work students need a well-defined concept of group and community practice in order to provide the range and quality of services that are required for social work practice in the 21st's century global community paradigm. Social work cannot be done in a mechanical and unthinking way. It is therefore necessary to have a knowledge base for practice. Therefore it is necessary to incorporate research based community practice in social work education. The present study describes two case studies which emphasize the constructive way of dealing with community by Community medicine Department in Kasturba Medical College, Manipal and an International NGO, World Vision.
Keywords: Community Practice; Research; Social work Education